Training beneficiaries in the PABRA Project - Andriatsitohaina, Muthoni R; Nagadya, Resty; Obilil, Innocent; Musoni, Augustine; Sefume, Lesole; Amane, Manuel; Fourie, Deidre; Herimihamina, Andriamazaoro; Kilango, Michael; Mutari, Bruce; Kennedy, Muimui; Asibuo, James Y.; et al. (International Center for Tropical Agriculture, 2018)
Pan African Bean Research Alliance (PABRA) specifically invests finance, human resource and time in ensuring that the continents bean researchers and staff are up to date and relevant with skills they require. The data sets presented here have been assembled from multiple sources to provide and indicative position of skill and knowledge building initiatives by PABRA and its various partners. The data sets show the number of people trained between the year 2003 t0 2016. Though the data sets provide the numbers, discussion on capacity building as a whole is available in the capacity building section of the PABRA website.